2021
DOI: 10.1111/jfpp.15263
|View full text |Cite
|
Sign up to set email alerts
|

Lipid oxidation and color changes in beef stored under different modified atmospheres

Abstract: Refrigerated storage is a method of extending the shelf life of meat and maintaining its freshness. Unfortunately, meat can be stored under refrigerated conditions for a limited period of time due to progressive changes in color and oxidative changes in lipids (Huang & Ahn, 2019; Mungure et al., 2016). In order to achieve the desired quality and microbiological safety of meat, the conditions and technological parameters of cold storage should be adjusted to the types of raw material. The quality of fresh packa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Therefore, we can infer that under the action of oxygen in the environment and its enzymes, vitamins, proteins, lipids, nucleotides and other nutrients in duck eggs will be oxidized and hydrolyzed, resulting in the loss of nutrients. Similar findings were also reported in beef, and it was found that fatty acids in beef are oxidized after being preserved 39 . Furthermore, Mun et al .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, we can infer that under the action of oxygen in the environment and its enzymes, vitamins, proteins, lipids, nucleotides and other nutrients in duck eggs will be oxidized and hydrolyzed, resulting in the loss of nutrients. Similar findings were also reported in beef, and it was found that fatty acids in beef are oxidized after being preserved 39 . Furthermore, Mun et al .…”
Section: Discussionsupporting
confidence: 80%
“…Similar findings were also reported in beef, and it was found that fatty acids in beef are oxidized after being preserved. 39 Furthermore, Mun et al showed that the levels of free amino acids and hypoxanthine changed sharply in pufferfish under storage conditions. 40 Taken together with our findings, this implied that the loss of fatty acids and protein and other nutrients due to environmental impacts is a common phenomenon in the process of food preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Surface discoloration was observed by Alarcón et al [ 49 ] in deer burgers after 12 days of chilled storage. Changes in the values of color coordinates in meat products can be attributed to the oxidation of lipids and myoglobin [ 66 , 67 ], the growth of Enterobacteriaceae and Pseudomonas spp. [ 68 ] and a decrease in moisture retention [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Samples from SMB14, which started with an L* index of 89.20, showed significant changes for all temperatures when covered, but only at 40 • C when uncovered, recording values from 88.00 to 86.70. Colour is an important characteristic in food and can be used as an indicator of many quality points, including acceptability [36] and as a predictor of oxidation [37] and phytochemical content [38]. Lightness is an achromatic measurement, between black and white, with values from 0 to 100, with the range of greyscale between them.…”
Section: Changes In the Colour Of Smb Between The Initial And 10-week...mentioning
confidence: 99%